Rare nuclearities in Mn/oxo cluster chemistry: Synthesis and characterization of a mixed-valence {MnII/III11} complex bearing acetate and salicylhydroximate(-3) bridging/chelating ligands. (15th September 2021) - Koumousi, Evangelia S.; Lazari, Gerasimi; Grammatikopoulos, Spyridon; Papatriantafyllopoulou, Constantina; Manos, Manolis J.; Perlepes, Spyros P.; Tasiopoulos, Anastasios J.; Christou, George; Stamatatos, Theocharis C.
Graphical abstract: The 2:1:2 reaction between Mn(O2 CMe)2 ·4H2 O, salicylhydroxamic acid (shaH2 ) and Me4 NOH·5H2 O has afforded the mixed-valent compound (Me4 N)4 [Mn II 2 Mn III 9 O4 (O2 CMe)9 (shi)6 ] (1 ), which consists of four vertex-sharing {Mn III 3 (μ3 -O 2− )} 7+ triangular subunits linked to each other and the Mn II atoms through the oximato arms of six shi 3− and the carboxylate O-atoms of nine supporting MeCO2 − groups. Abstract: The one-pot reaction between Mn(O2 CMe)2 ·4H2 O, salicylhydroxamic acid (shaH2 ) and Me4 NOH·5H2 O in a molar ratio of 2:1:2, and a solvent mixture comprising MeCN and MeOH, affords the new mixed-valence cluster compound (Me4 N)4 [Mn II 2 Mn III 9 O4 (O2 CMe)9 (shi)6 ] (1 ) in moderate yields. The anion of the tetradentate (N, O, O, O) chelating/bridging ligand shi 3− resulted from the in-situ metal ion-assisted amide-iminol tautomerism of shaH2 . The [Mn II 2 Mn III 9 (μ3 -O)4 (μ-OR)3 (μ3 -NO)6 ] 14+ core of 1 comprises four vertex-sharing {Mn III 3 (μ3 -O 2− )} 7+ triangular subunits of different types, which are linked to each other and the Mn II atoms through the oximato arms and the carboxylate O-atoms of six η 1 :η 1 :η 1 :η 2 :μ3 shi 3− and three η 1 :η 2 :μ3 MeCO2 − groups, respectively. Peripheral ligation about the core is provided by six η 1 :η 1 :μ MeCO2 − groups and the chelating parts of the shi 3− ligands. Solid-state direct-current (dc) magnetic susceptibility studies revealed the presence of predominant antiferromagnetic exchange interactions between the Mn centers, mainly promoted by the coplanarity of the μ3 -O 2− within the Mn3 triangular planes and the insignificant distortion of the MnNOMn bridging units. Low-lying excited states precluded obtaining a good fit from the magnetization data, and the ground state was instead determined from the alternating-current (ac) data, which indicated an S = 3 ground state for 1 . The combined results emphasize the continuing supply from the use of the salicylhydroxime chelating/bridging ligand of new 3d-metal clusters of very rare nuclearities and beautiful molecular structures.